Transformation of Strawberry "Festival" to sweet and determination of physical and physical-chemical parameters - Quesada Matos, Romilio L.; Quesada González, Omaida; Castellanos Parra, Raúl; Cantos Macías, Manuel Angel; Savilolo Josias, Alceu Filipe (Revista Cubana de Química, 2021)
This work evaluates the physical and physicochemical parameters of the “Festival” strawberry variety, obtained under the edaphoclimatic conditions of Humpata, Province of Huila, Angola, followed by its transformation into sweet of adequate quality. The analyzes carried out were: the mass was determined on analytical balance and the transversal and longitudinal diameters with a caliper. Other analyzes were: total acidity titratable by volumetry, pH by potentiometry, total soluble solids by refractometry, moisture and ash by gravimetry. The study carried out showed that the pH of the pulp was 3.41; and in the sweet it was 3.31. The titratable acidity in the strawberry pulp was 0.186 g/100 ml and in the sweet 0.096 g/100 ml; the ascorbic acid content in the pulp was 18.60 mg/100g. The average content of soluble solids in the pulp was 9.51ºBrix and for the sweet 68.83ºBrix. These chemical characteristics of the pulp and the sweet provide information about their nutritional values.